Effects of modified brief counseling-5A on illness perception, compliance with medication, and fasting blood sugar levels of diabetes mellitus patients - Neni Probosiwi; Akrom Akrom; Titiek Hidayati; Ginandjar Zukhruf Saputri (Universitas Ahmad Dahlan, 2020)
Diabetes mellitus is a degenerative disease with persistently increasing prevalence. When patients lack knowledge of their illness and compliance with oral drug therapy, it can lead to treatment failure. This study aims to determine the effect of counseling on disease perception and medication adherence for patients with diabetes mellitus. This prospective observational cohort study aimed to determine the effects of counseling on illness perception and adherence to medication among patients with diabetes mellitus. A sample of 72 patients was selected by consecutive sampling technique and, then, evenly divided into two, namely counseling group and non-counseling group. The data were collected prospectively through observation, interview, brief counseling with the 5A strategies, and questionnaire survey. The result show that counseling had a significant effect on illness perception (p=0.000). Counseling had a significant effect on adherence to medication (p=0.027). Counseling had a significant effect on lowered blood sugar levels (p=0.028). Conclusion: counseling is believed to be able to reduce patientsâ€™ negative perceptions of diabetes mellitus and, consequently, increase adherence to oral drug consumption.Â